Pelatihan Analisis Data Komputasional untuk Mendukung Riset Akademik bagi Mahasiswa Pendidikan Guru Pendidikan Anak Usia Dini - Azi Matur Rahmi; Yossi Srianita; Pupung Purnamasari; Endang Citrowati; Rully Indiarti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Training in computational data analysis serves as an effort to enhance students' competence in effectively processing, analyzing, and interpreting research data. This activity is designed for students of the Early Childhood Teacher Education (PGPAUD) program to equip them for the preparation of final projects and the conduct of academic research. The training employs a combination of lectures, demonstrations, hands-on practice, and guided support, utilizing relevant data analysis software. The curriculum covers an introduction to computational quantitative and qualitative data analysis, data processing, data visualization, and the interpretation of analysis results. Training outcomes indicate an improvement in participants' understanding and skills regarding the use of computational data analysis tools to support the research process. Furthermore, participants demonstrated increased confidence in independently processing research data and producing more systematic research reports. Consequently, this training contributes to strengthening the research capacity of PGPAUD students and supports the improvement of the quality of academic work within the higher education environment.